Identification of Subtle Verbal Memory Deficits in Premanifest Huntington Disease Using the California Verbal Learning Test. Issue 1 (March 2020) - Holden, Heather M.; Tierney, Savanna M.; Graves, Lisa V.; Beltran-Najera, Ilex; Woods, Steven Paul; Snell, Chase M.; Delis, Dean C.; Corey-Bloom, Jody; Gilbert, Paul E.
Abstract : Background: Verbal memory impairment in individuals with Huntington disease (HD) is well-documented; however, the nature and extent of verbal memory impairment in individuals with premanifest HD (pre-HD) are less understood. Objective: To evaluate verbal memory function in individuals with pre-HD by comparing their performance on the California Verbal Learning Test to that of individuals with a clinical diagnosis of HD and that of a demographically similar group of adults with no family history of, or genetic risk for, HD, thereby reducing possible complications of psychiatric difficulties commonly experienced by individuals who are at risk for HD but are gene negative. Methods: Participant groups included 77 adults with a diagnosis of HD, 23 premanifest gene carriers for HD (pre-HD), and 54 demographically similar, healthy adults. The California Verbal Learning Test—Second Edition (CVLT–II) was used to evaluate the participants' immediate and delayed recall, recognition, learning characteristics, errors, and memory retention. Results: The pre-HD group performed significantly worse than the healthy group, yet significantly better than the HD group, on Short and Long Delay Recall (Free and Cued) and Recognition Discriminability. On Total Immediate Recall, Learning Slope, Semantic Clustering, and Intrusions, the pre-HD group performed similarly to the healthy group and significantly better than the HD group. None of the groups differed in their performance on Repetitions and a measure of retention. Conclusions: Subtle memory deficits can be observed during the premanifest stage of HD with use of a subset of indices from the CVLT–II.